La vegetación del delta del Ebro (V): las comunidades helofíticas e hidrófilas (Clases Phragmiti-Magnocaricetea y Molinio-Arrhenatheretea) - Curcó i Masip, Antoni (Lazaroa, 2001)
The helophytic communities of the Ebro delta are notably rich due to the surface area they cover and the high spatial variability of the main ecological parameters (salinity and water regime). Eight associations of the class Phragmiti-Magnocaricetea have been recognised, as well as a community of Sparganium erectum subsp. Neglectum, whose status is uncertain due to the few samples obtained. Of them, Galio elongati-Caricetum acutiformis is proposed as new, and a new status is suggested for Helosciadetum nodiflori polypogonetosum monspeliensis (=Polypogono monspeliensis-Nasturtietum officinalis Carretero & Boira 1984). The class Molinio-Arrhenatheretea is poorly represented by the single association: Holoschoenetum.